UPAYA PENINGKATAN BISNIS DENGAN DIGITAL BRANDING PEMBUATAN LOKASI UMKM MELALUI APLIKASI GOOGLE MAPS DI DESA SIRNAJAYA - Setyawan, Dhiwa Harum; Cahyati, Ari Dewi; Putra, Purnama (An-Nizam, 2024)
This activity is carried out to help install Google Maps pins. Some features that can help MSMEs are directions, sharing locations, and reviews that can be accompanied by images. With these features, the public can access searches and provide ratings, so that MSMEs can optimize branding and add addresses, telephone numbers, place categories, and store operating hours, which will increase consumer interest.      This community service activity is carried out using a community empowerment system method in the form of socialization and mentoring. The results of the implementation of community service are the successful registration of business locations in Sirnajaya Village MSMEs, providing complete and actual MSME information, and appearing in searches when consumers search for relevant products. In addition, reviews and ratings from experienced customers can provide strong social evidence that can increase the trust and interest of potential customers so as to increase sales.